Spacetimes Admitting Concircular Curvature Tensor in f(R) Gravity - De, Uday Chand; Shenawy, Sameh; Abu-Donia, H. M.; Turki, Nasser Bin; Alsaeed, Suliman; Syied, Abdallah Abdelhameed (Frontiers in Physics, 2022)
The main object of this paper is to investigate spacetimes admitting concircular curvature tensor in f(R) gravity theory. At first, concircularly flat and concircularly flat perfect fluid spacetimes in % f( R) gravity are studied. In this case, the forms of the isotropic pressure p and the energy density σ are obtained. Next, some energy conditions are considered. Finally, perfect fluid spacetimes with divergence free concircular curvature tensor in f(R) gravity are studied; amongst many results, it is proved that if the energy-momentum tensor of such spacetimes is recurrent or bi-recurrent, then the Ricci tensor is semi-symmetric and hence these spacetimes either represent inflation or their isotropic pressure and energy density are constants.